Pengaruh Motivasi Kerja dan Pelaksanaan Fungsi Manajemen Keuangan atas Pengelolaan Pendapatan Negara Bukan Pajak (PNBP) Terhadap Pelaksanaan Akuntabilitas Keuangan Pemerintah Kota Makassar - Dian Kurniawan; Patiware, Andi (Insan Cita Bongaya Research Journal, 2023)
This study aims to examine the effect of work motivation on the implementation of the financial management function in the management of non-tax revenue (PNBP) and its impact on the implementation of financial accountability for the government of Makassar City both jointly (simultaneously) and individually (partially). Respondents in this study were employees at the Makassar City Cooperative Service. Based on quantitative research methods, the total sample in this study was 44 respondents. In this study using primary data obtained from distributing questionnaires. The number of questionnaires distributed was 44 copies. The analytical method used in this study is multiple regression. The results of this study indicate that Work Motivation and the Implementation of the Financial Management Function simultaneously have a positive and significant effect on the Implementation of Financial Accountability at the Makassar City Government Office.